1988
DOI: 10.1111/j.1399-3054.1988.tb09193.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐wall lysing enzymes and products of cell‐wall digestion elicit ethylene in citrus

Abstract: Cell-wall lysing enzymes and products of cell-wall digestion elicit ethylene in citrus. -Physiol. Plant. 73: S W .Ethylene production was induced in Valencia oranges [Citrus sinensis (L.) Osheck] by injection of the fungal enzyme mixture Pectolyase (Aspergillus juponicus) which contains pectolytic enzymes into the peel. The mixture also stimulated production of I -aminocyclopropane-1-carboxylic acid (ACC). Cycloheximide partially inhibited the Pectolyase-induced ethylene response. Pectin fragments, resulting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…These diplodia-produced enzymes could contribute to fruit abscission directly by degrading the cell wall and middle lamella in the abscission zone, and they may also indirectly impact fruit abscission by inducing the fruit to produce ethylene, which in turn induces the plant abscission zone to produce cell wall-degrading enzymes. It has been reported that the fungal pectolytic enzymes and their products induce ethylene in citrus (63) and tomato (64,65) fruits.…”
Section: Figmentioning
confidence: 99%
“…These diplodia-produced enzymes could contribute to fruit abscission directly by degrading the cell wall and middle lamella in the abscission zone, and they may also indirectly impact fruit abscission by inducing the fruit to produce ethylene, which in turn induces the plant abscission zone to produce cell wall-degrading enzymes. It has been reported that the fungal pectolytic enzymes and their products induce ethylene in citrus (63) and tomato (64,65) fruits.…”
Section: Figmentioning
confidence: 99%
“…Ethylene biosynthesis, one common response of plant tissues to pathogen attack (21), is stimulated by a variety of plant-and pathogen-derived polysaccharides and proteins (4,26,28). Ethylene has been suggested to play a role in activating certain defense responses in some plant tissues (9).…”
Section: Introductionmentioning
confidence: 99%
“…Baldwin and Biggs (3) reported that Pectolyase induces ethylene production in citrus fruit. We found that the mixture of enzymes in Pectolyase is also effective in inducing ethylene formation in tomatoes.…”
Section: Effects Of the Enzymes On Ethylene Productionmentioning
confidence: 99%